Chemometric classification of geothermal and non-geothermal ethanol leaf extract of seurapoh (Chromolaena odorata Linn) using infrared spectroscopy. Issue 1 (February 2021) - Abubakar, A; Yusuf, H; Syukri, M; Nasution, R; Karma, T; Munawar, A A; Idroes, R
Abstract: This work reports on the chemometric classification of ethanol leaf extract of seurapoh ( Chromolaena odorata Linn ) obtained from geothermal and non-geothermal area. This analysis aims to identify the correlation between the ethanol leaf extract of seurapoh (ELES) collected from three locations, one geothermal area (Ie Seuum) and two non-geothermal areas (Lhoknga Beach, Samahani), Aceh Besar Province, Indonesia. The extraction was made by ethanol 96% using maceration. After extraction, each sample's infrared spectrum was acquired using near-infrared (NIR) spectroscopy at a wavenumber range of 10, 000 cm -1 – 4, 000 cm -1 . The spectral data were preprocessed with the MSC method to remove the light scattering effect during spectral acquisition. The classification of ELES was conducted using Principle Component Analysis (PCA), yielding plot scores as follows, PC1 and PC2 were capable of explaining 97% of the total data (PC1 = 87%, PC2 = 10%). The results also revealed very well discrimination of the samples based on their respective sampling locations. It further implied that the ELES had significant different NIR spectral profiles, which were following their sampling locations. Hence, it can be concluded that there is a possibility of different compounds contained within the ELES, collected from the geothermal area and two other non-geothermal areas.